PENINGKATAN KOMPETENSI KERJA MELALUI INTERVENSI PELATIHAN - Masduki Masduki (Universitas Negeri Jakarta, 2017)
This research aimed at testing and analyzing the influence of training intervention on the improvement of employees’ work competence in globalization era. This research used correlation survey method between independent variable of training intervention (X) and dependent variable of working competence (Y). Regression analysis was used to determine the correlation model between independent variable Y (work competence) and dependent variable, training intervention (X), whereas correlation analysis was used to determine the strength or weakness between Y variable (working competence) and X (training competence). The target population in this research is the employees of Kimia Farma Apotek in Depok City business unit, the level of employees in this research are assistant manager, supervisor, and clerks. The total number of population is 96 employees; the entire population is also the entire sample. The data collection instrument is Likert scale questionnaire. The result of the research are: a) in this advance information and technological era, training still gives positive and strong influence to improve the working competence of the employees, especially related to improvement of motivation to achieve organizational targets and objectives; b) improvement of employees’ working competence through training can be predicted by using the simple regression model of Y= 0,878 + 0,777 X; c) training gives 45.5% influence toward the improvement of employees’ working competence and the rest 55.5% is predicted by other factors such as, working environment, leaders’ support, reward system, facilities and infrastructure support, etc.